Écriture de soi ou le sujet posé en objet - Tomaszewski, Marek (Archiwum Emigracji. Studia – Szkice – Dokumenty, 2018)
SELF-WRITING, THAT IS THE SPEAKING I OBJECTIFIED Kazimierz Brandys experiments in his prose by applying many genres, such as the crypto-biography, metafiction, epistolary novel, radio interview, reportage, note to the editor, screenplay, etc. What is also outstanding in his writings are elements characteristic of the essay, the aesthetics of the fragmentary and the montage of pieces of other texts. From the mid-1970s Kazimierz Brandys also tries to combine fiction with elements of the documentary and autobiography. The article offers an interpretation of his Przygody Robinsona [Robinson’s Adventures] (1999), which appears to a certain extent as a return to literary fiction. PISANIE O SOBIE (SOBĄ), CZYLI PODMIOT MÓWIĄCY UPRZEDMIOTOWIONY Proza Kazimierza Brandysa ujawnia liczne eksperymenty narracyjne. Przybiera ona formy gatunkowe takie jak kryptobiografia, metapowieść, powieść epistolarna, wywiad radiowy, reportaż, nota do wydawcy, scenariusz filmowy itp. Charakterystyczna jest dla niej także eseizacja narracji, estetyka fragmentu, montaż utworu z kawałków innych tekstów. Mniej więcej od połowy lat 70. autor Nierzeczywistości i Ronda próbuje systematycznie łączyć formułę wypowiedzi powieściowej z dokumentaryzmem i autobiografią. Artykuł zawiera interpretację utworu Przygody Robinsona (1999), który jawi się jako częściowy powrót do literackiej fikcji.